Determining soil health parameters controlling crop productivity in a Citrus Greening disease affected orange grove - Sean C. Stokes; Pankaj Trivedi; Kristen Otto; James A. Ippolito; Thomas Borch (Elsevier, 2023)
Soil health is an important aspect for maintaining adequate crop production, but the specifics of what entails a healthy soil can vary from region to region and crop to crop. In highly managed agricultural systems, unhealthy soil can be masked by intensive management practices, yet there must be detrimental cutoff points in various characteristics, such as soil organic matter (SOM) concentrations, where even highly managed systems start to lose productivity. This negative impact was observed in a Florida citrus grove containing Valencia orange trees with observable differences in tree size yet were otherwise managed identically. A soil health index demonstrated that the areas with smaller trees had a significantly lower index score and those soils contained significantly less SOM (average SOM ​= ​0.57%) compared to areas with larger trees (average SOM ​= ​0.94%). The areas of lower crop productivity also had less enzymatic activity of common carbon-cycling enzymes and different microbial populations, which all together negatively affected soil health and corresponding plant productivity. This agricultural region is also known to have a Citrus Greening disease (HLB) infection rate of close to 100%, hence we developed a hypothesis that could explain how progression of this infection could be impacted by SOM concentrations and differences in microbial diversity. We posit that areas of this grove with healthier soil could have more resistance to the onset of fatal HLB symptoms. Consequently, soil organic matter distribution and concentration should be considered when establishing new groves in order to optimize soil and crop productivity.